Lack of Associations between Body Mass Index and Clinical Outcomes in Patients with Papillary Thyroid Carcinoma - Kwon, Hyemi (Endocrinol Metab (Seoul), 2015)
BACKGROUND: Obesity is associated with aggressive pathological features and poor clinical outcomes in breast and prostate cancers. In papillary thyroid carcinoma (PTC), these relationships remain still controversial. This study aimed to evaluate the associations between body mass index (BMI) and the clinical outcomes of patients with PTC. METHODS: This retrospective study included 1,189 patients who underwent total thyroidectomy for PTCs equal to or larger than 1 cm in size. Clinical outcomes were evaluated and compared based on the BMI quartiles. RESULTS: There were no significant associations between BMI quartiles and primary tumor size, extrathyroidal invasion, cervical lymph node metastasis, or distant metastasis. However, an increase in mean age was associated with an increased BMI (P for trend <0.001). Multifocality and advanced tumor-node-metastasis (TNM) stage (stage III or IV) were significantly associated with increases of BMI (P for trend 0.02 and <0.001, respectively). However, these associations of multifocality and advanced TNM stage with BMI were not significant in multivariate analyses adjusted for age and gender. Moreover, there were no differences in recurrence-free survivals according to BMI quartiles (P=0.26). CONCLUSION: In the present study, BMI was not associated with the aggressive clinicopathological features or recurrence-free survivals in patients with PTC.